Revealing Cultural Causes of Fraud: An Ethnographic Study in Public Company - Dinata, Ruri Octari; Irianto, Gugus; Mulawarman, Aji Dedi (Jurnal Economia, 2018)
Abstract: Revealing Cultural Causes of Fraud: An Ethnographic Study in Public Company. This ethnographic study aimed to reveal the cultural causes of fraud in public company. The data was obtained from direct observation and interview to the research site at Public Company X, located in Medan City of North Sumatra. This study found that existence of a culture of "all can be arranged" as well as a culture of "procedure only formality" can ultimately lead to fraud. Keywords: fraud, public company, ethnography, culture of all can be arranged, culture of procedure only formalityAbstrak: Menyingkap Budaya Penyebab Fraud: Studi Etnografi di Badan Usaha Milik Negara. Penelitian ini bertujuan untuk menyingkap budaya penyebab fraud di BUMN dengan studi etnografi sebagai metodologi penelitiannya. Data diperoleh dari observasi langsung ke situs penelitian di BUMN X yang terletak di Kota Medan Sumatera Utara dan melakukan wawancara dengan informan di situs penelitian tersebut. Hasil penelitian menunjukkan adanya budaya “semua bisa diatur” serta budaya “prosedur hanya formalitas” yang akhirnya dapat menjadi pemicu terjadinya fraud. Kata kunci: fraud, BUMN, etnografi, budaya semua bisa diatur, budaya prosedur hanya formalitas